Respuesta :
Because there are two minus signs in the middle of 6 and 3, those two minus signs can be converted to a plus sign.
-6 - (-3) = -6 + 3
-6 + 3
So, -3 is the answer.
-6 - (-3) = -6 + 3
-6 + 3
So, -3 is the answer.
the answer to this question is -3 since 2 negatives = a + and a - and a + equal a -
so here since we have -6 - -3 we switch 3 signs 3 becomes positive -6 + 3=-3
and there's your answer
so here since we have -6 - -3 we switch 3 signs 3 becomes positive -6 + 3=-3
and there's your answer